Some findings on the design and implementation of mathematics tutorials at a university - Maharaj, Aneshkumar (South African Journal of Higher Education, 2016)
This paper reports on the design and effectiveness of four tutorial types in the context of first year mathematics tutorials, at a South African university for the period 2003 to 2011. A model for the design of mathematics tutorials was formulated. This model informed the design, implementation and refining of the mathematics tutorials over the nine year period. It was found that mathematics students get greater benefit from tutorials that are more organized and include a completion of homework unit requirement.